Factors Influencing MSMEs' Interest in E-commerce Transactions and Their Effect on MSMEs' Income During the Covid-19 Pandemic - Ikhsan Habib Fabillah; Hendra Prasetyo (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2024)
Currently, the use of e-commerce is increasingly popular, especially in the last few years implementation of PSBB, micro-scale PPKM, Work From Home (WFH), Social Distancing, and others throughout the pandemic requires changes in people's lifestyles. The behavior of sellers and buyers is starting to change. With the public being prohibited from mobilizing during the pandemic, business actors have turned to online media. The aim of this research is to determine the factors that influence MSMEs' interest in transacting in e-commerce and their influence on MSMEs' income. The sample in this research was 45 MSMEs in the city of Bandar Lampung. The data collection technique was carried out by distributing questionnaires which were distributed directly to respondents. Data processing uses SPSS. The results of this research found that perceptions of usefulness, convenience, and trust influence MSMEs' interest in transacting in e-commerce, and social factors do not influence MSMEs' interest in transacting in e-commerce, then MSMEs' interest in transacting in e-commerce can influence MSME income.